Evaluation of Village Fund Planning and Budgeting for Infrastructure Development in Lamunga Village - Yunita, Ahlam; Septika, Baiq Herdina; Kartikaningrum, Sari (Mandalika Journal of Economics, Management, and Accounting, 2026)
This study aims to analyse the planning and budgeting processes of Village Funds and their effectiveness in supporting rural infrastructure development in Lamunga Village, West Sumbawa Regency. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the Village Head, village officials, Treasurer, and Village Consultative Body. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques. The results indicate that Village Fund management has been implemented through planning, budgeting, implementation, and evaluation stages in accordance with Regulation of the Minister of Home Affairs No. 20 of 2018. Infrastructure development planning was conducted participatively through village deliberations. The effectiveness of Village Fund utilization is reflected in the 100 percent realization rate of infrastructure budgets and the tangible benefits for community welfare).